2018
DOI: 10.1002/rsa.20773
|View full text |Cite
|
Sign up to set email alerts
|

Scaling limits of random bipartite planar maps with a prescribed degree sequence

Abstract: We study the asymptotic behavior of uniform random maps with a prescribed face-degree sequence, in the bipartite case, as the number of faces tends to infinity. Under mild assumptions, we show that, properly rescaled, such maps converge in distribution toward the Brownian map in the Gromov-Hausdorff sense. This result encompasses a previous one of Le Gall for uniform random q-angulations where q is an even integer. It applies also to random maps sampled from a Boltzmann distribution, under a second moment assu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…This result has been extended by Le Gall [45] to critical sequences q such that the degree of a typical face has exponential moments (while the first results on this model were obtained by Marckert & Miermont [49]). The result also holds for critical sequences q such that the degree of a typical face has a finite variance, as shown in the recent work [51] (such a sequence is called generic critical, see Section 2.1 for precise definitions). Convergence towards the Brownian map has also been established in the non-bipartite case in [52,54].…”
Section: Introductionmentioning
confidence: 53%
“…This result has been extended by Le Gall [45] to critical sequences q such that the degree of a typical face has exponential moments (while the first results on this model were obtained by Marckert & Miermont [49]). The result also holds for critical sequences q such that the degree of a typical face has a finite variance, as shown in the recent work [51] (such a sequence is called generic critical, see Section 2.1 for precise definitions). Convergence towards the Brownian map has also been established in the non-bipartite case in [52,54].…”
Section: Introductionmentioning
confidence: 53%
“…After the seminal papers [MM06, LG07], Le Gall [LG13] and Miermont [Mie13] proved that uniform quadrangulations have a scaling limit, the Brownian map. This convergence was later extended to generic critical sequences in [Mar18b], building on the earlier works [MM07,LG13]. In 2011, Le Gall and Miermont [LGM11] established the subsequential convergence of non-generic critical Boltzmann maps.…”
Section: Application To Random Planar Mapsmentioning
confidence: 88%
“…It was proved independently in [43] for quadrangulations and in [33] for more general cases including triangulations, that several important classes of random planar maps converge in this sense toward a limiting random compact metric space called the Brownian map, which had been introduced previously in [40]. Several recent papers (see in particular [1,4,9,41]) have shown that many other classes of random planar maps converge to the Brownian map, which thus provides a universal continuous model of random geometry in two dimensions. On the other hand, in a series of recent papers [45,46,47,48], Miller and Sheffield have shown that the Brownian map can be equipped with a conformal structure, which is linked to Liouville quantum gravity, and that this conformal structure is in fact determined by the Brownian map viewed as a random metric space.…”
Section: Introductionmentioning
confidence: 95%